Avaliação do risco à perda da qualidade ambiental do aquífero freático na região metropolitana de Goiânia - Nogueira, Sérgio Henrique de Moura (2017)
Among the impacts caused in nature by human society, urbanization is considered one of the most aggressive, and in many cases may be irreversible. In the last decades, the majority of the global population has been living in urbanized areas, generating megacities and metropolitan areas with high demographic density, where several activities have intensified and can threat the environment as a whole, including aquifers. The loss of the environmental quality of groundwater is a common problem in Brazilian urban centers. Studies that approaches the spatialisation of impacts from exposure to pollutant loads of different natures, are important instruments for directing actions aimed at the conservation of water resources in these large urban centers. In this study, a map of water table's depth was elaborated from the processing of multiple variables. Then, an environmental vulnerability assessment was elaborated, and from the categorization of the land use, it was possible to obtain a classification map of the general risk of loss of the environmental quality of the groundwater of the metropolitan region of Goiânia. The resulting map shows the places where the risks are high and very high, coinciding with the urbanized areas, explained by the intensity of activities that threaten the natural resource. In the non-urbanized areas there are places of moderate risk, explained by the establishment of agricultural and livestock activities where the water table is near the surface.